Perlindungan Merek Kosmetik Wardah Ditengah Pemasaran Pada Era Ekonomi Digital - Zhafira Gitamo; Asep Saripudin (Peneliti.net, 2023)
Trademark Law to overcome and anticipate fraud in the use of trademarks. Trademark law in Indonesia adheres to the first to file system, which means whoever registers or obtains a trademark certificate first, is the one who has the right to the mark, then other parties may not register a product with the same mark. The Wardah brand has become very well known to the wider community with its slogan, namely inspiring beauty. Wardah's promotional techniques include advertising, sales promotion, direct marketing, personal selling and public relations as a way to introduce Wardah's brand to the public and provide discount vouchers on every e-commerce platform as a technique to attract consumer interest. The purpose of this paper is to determine the form of protection for well-known brands in Indonesia and to understand the role of the digital economy in marketing the brand or brand of Wardah cosmetics so that it is known to the public. This research uses normative juridical research methods.